Bratton's Family Medicine Board Review, 3rd Edition - Bratton, Robert L (Lippincott Williams & Wilkins, 2007)
Bratton's Family Medicine Board Review, Third Edition, is a directed review of important topics that typically appear on American Board of Family Medicine (ABFM) in-training examinations, board certification examinations, and recertification examinations. This material is not intended for a comprehensive review but, instead, should direct the examinee to areas of weakness that may need further review. Family medicine is a broad field, and to provide a complete, comprehensive review of all topics that may be covered is extremely time consuming if not impossible. Several other courses attempt to provide this type of review; however, this book is more abbreviated and focuses on topics that are commonly found on board examinations. Adequate preparation for any test is the key to success and rewarding results. Given this, we all know the importance of practice tests and the benefits of testing our knowledge base before the actual examination. This review book is structured for the examinee with limited time and resources for review and should be used only by those individuals with an established foundation of knowledge within the field of family medicine. Its primary purpose is to identify areas of weakness that can be improved on. Each edition attempts to update the existing information and revise any changes that have occurred in the medical field. The ABFM restructures the examination on a yearly basis, so it is important to visit its Website, www.theabfm.org, to get updates on the structure of each examination. I hope that you will find this book enlightening and, most of all, beneficial in your studies for the ABFM examinations.